The application of the state financial losses' assessment in corruption crime after the verdict of the constitutional court no. 31/puu-x/2012 - Sadat, Anwar (Library of Sultan Agung Islamic University, 2022)
The corruption cases in Indonesia are considered as a crime which is increasingly worrying since it causes state losses, even in its development the value of losses suffered by the Indonesia state are getting increased. This study aims to find out the application of the state financial losses’ assessment in corruption crime’s verdict. This study is a normative legal study using a statutory approach, conceptual approach, and comparative approach. The legal materials are used such as primary material (the corruption law), secondary materials (book and journal), and tertiary materials (law dictionary and Indonesian dictionary). The technique of legal material collection is carried out by studying literature, while the analytical technique is carried out using the interpretation method. The results of the study show that in the context of assessing the state losses, not all the cases being tried which are related to corruption crime, must go through an audit process of BPK or BPKP. When the calculation and the determination of the state losses are easy to calculate, it is only needed to be done by an investigator or prosecuting attorney. Thus, the calculation and the determination of the state financial losses is only carried out if needed, or when the statements of the experts are entered, to add or to give their statements before the trial.